Endothelial cells from umbilical cord of women affected by gestational diabetes: A suitable in vitro model to study mechanisms of early vascular senescence in diabetes. Issue 6 (27th May 2021) - Di Tomo, Pamela; Alessio, Nicola; Falone, Stefano; Pietrangelo, Laura; Lanuti, Paola; Cordone, Valeria; Santini, Silvano Junior; Di Pietrantonio, Nadia; Marchisio, Marco; Protasi, Feliciano; Di Pietro, Natalia; Formoso, Gloria; et al.
Abstract: Human umbilical cord endothelial cells (HUVECs) obtained from women affected by gestational diabetes (GD‐HUVECs) display durable pro‐atherogenic modifications and might be considered a valid in vitro model for studying chronic hyperglycemia effects on early endothelial senescence. Here, we demonstrated that GD‐ compared to C‐HUVECs (controls) exhibited oxidative stress, altered both mitochondrial membrane potential and antioxidant response, significant increase of senescent cells characterized by a reduced NAD‐dependent deacetylase sirtuin‐1 (SIRT1) activity together with an increase in cyclin‐dependent kinase inhibitor‐2A (P16), cyclin‐dependent kinase inhibitor‐1 (P21), and tumor protein p53 (P53) acetylation. This was associated with the p300 activation, and its silencing significantly reduced the GD‐HUVECs increased protein levels of P300 and Ac‐P53 thus indicating a persistent endothelial senescence via SIRT1/P300/P53/P21 pathway. Overall, our data suggest that GD‐HUVECs can represent an "endothelial hyperglycemic memory" model to investigate in vitro the early endothelium senescence in cells chronically exposed to hyperglycemia in vivo.